Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Pada Dinas Tenaga Kerja Kota Tangerang Selatan - Muhamad Farhan Maulana; Yeni Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study aims to analyze the effect of workload and work stress on employee performance at the Department of Manpower of South Tangerang City. The background of this research is based on findings related to work stress and employee initiative, as well as the condition of employee performance that has not been optimal. This study employs a quantitative approach with an associative research design. The sample consists of the entire population of 90 employees using a saturated sampling technique. Data were collected through questionnaires and analyzed using simple and multiple linear regression, as well as t-tests and F-tests with the assistance of SPSS version 25. The results show that the workload variable (X₁) has a significant partial effect on employee performance (Y), with a t-value of 7.104 > t-table 1.987 and a significance value of 0.000 < 0.05, contributing 36.4% (R² = 0.364) to employee performance. The work stress variable (X₂) also has a significant partial effect, with a t-value of 8.551 > t-table 1.987 and a significance value of 0.000 < 0.05, contributing 45.4% (R² = 0.454). Simultaneously, both variables X₁ and X₂ have a significant effect on employee performance, with an F-value of 41.598 > F-table 3.10 and a significance value of 0.000 < 0.05. The simultaneous coefficient of determination is 48.9% (R² = 0.489), indicating that workload and work stress together explain 48.9% of the variation in employee performance, while the remaining 51.1% is influenced by other factors not examined in this study. In conclusion, both workload and work stress have significant effects, either partially or simultaneously, on employee performance. Therefore, adjusting workload conditions and optimally managing work stress are essential to improving employee performance.